Genomic surveillance of SARS-CoV-2 in the Republic of Congo. (April 2021) - Ntoumi, Francine; Mfoutou Mapanguy, Claujens Chastel; Tomazatos, Alexandru; Pallerla, Srinivas Reddy; Linh, Le Thi Kieu; Casadei, Nicolas; Angelov, Angel; Sonnabend, Michael; Peter, Silke; Kremsner, Peter G.; Velavan, Thirumalaisamy P.
Highlights: First report on SARS-CoV-2 diversity from the Republic of Congo. SARS-CoV-2 genomes carried the spike mutation D614G. SARS-CoV-2 genomes found to belong to lineage B1 and Nextclade 20A and 20C. Two separate introductions of the SARS-CoV-2 virus in the Republic of Congo. Abstract: Objective: The aim of this study was to carry out whole-genome sequencing (WGS) of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), using samples collected from Congolese individuals between April and July 2020. Methods: Ninety-six samples were screened for SARS-CoV-2 using RT-PCR, and 19 samples with Ct values <30 were sequenced using Illumina Next-Generation Sequencing (NGS). The genomes were annotated and screened for mutations using the web tool 'coronapp'. Subsequently, different SARS-CoV-2 lineages were assigned using PANGOLIN and Nextclade. Results: Eleven SARS-CoV-2 genomes were successfully sequenced and submitted to the GSAID database. All genomes carried the spike mutation D614G and were classified as part of the GH clade. The Congolese SARS-CoV-2 sequences were shown to belong to lineage B1 and Nextclade 20A and 20C, which split them into distinct clusters, indicating two separate introductions of the virus into the Republic of Congo. Conclusion: This first study provides valuable information on SARS CoV-2 transmission in the central African region, contributing to SARS CoV-2 surveillance on a temporal and spatial scale.